Responsabilidad familiar y estatal en los casos de reclutamiento forzado de niños, niñas y adolescentes en el marco del conflicto armado colombiano: Principio de corresponsabilidad - Ortega Galindo, Doris Mercedes (2022)
It is relevant to elucidate a regrettable phenomenon within the armed conflict in Colombia: the illicit recruitment of children and adolescents, a situation that has plagued the Colombian territory for more than 60 years. This event occurs due to the non-compliance with the duty to protect the rights of children and adolescents by the State and the family, in accordance with the co-responsibility that exists between both institutions, which failed to watch over the rights of this specific population. In that regard, the main objective of this research is to determine the impact derived from the failure of the Colombian State and the family to protect the rights of children and adolescents, as a decisive factor in the forced recruitment by armed groups outside the law. Thus, the type of research is legal-dogmatic, the approach is qualitative, the techniques for data collection were the registry file and data systematization; the method for analyzing the information collected is the analytical-synthetic one. In the end, it was concluded that the family and the Colombian State are responsible for allowing children and adolescents to be forcibly recruited and subjected to violent spaces where their rights and guarantees did not exist.